Unemployment and Informality in Costa Rica: Facing the Fourth Industrial Revolution - Benavides Vindas, Shirley (2022)
Unemployment and informal economy in Costa Rica have been discussed nationwide in terms of their origins, consequences, and their meaning for the well-being and development of the country. For this reason, this article aims to analyze whether the country is prepared to face the fourth industrial revolution within the framework of unemployment and informality. For this, a review of secondary sources such as official databases and bibliographic information from centers and institutes of international reference for Latin America was carried out. It was determined that new projects must be accompanied by productive investments that reduce unemployment and informality, avoid precarious employment, and stop the social exclusion that characterize the Costa Rican productive structure. On the other hand, the success of the fourth industrial revolution must be linked to the design and implementation of public policies that enable transformations and allow more efficient progress for inclusive development. The main conclusion is that the country does not have a dedicate strategy to adapt to the fourth industrial revolution´s changes, which would enable high dynamism and development opportunities.